PERGESERAN MAKNA DARI NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA KE ADAPTASI FILMNYA KARYA KUNTZ AGUS (Kajian Ekranisasi) - Citra Annisa, - (2017)
This study aims to describe the structure of the story, to describe the facts of the story and the means of literature, to describe the different meaning from the novel Surga Yang Tak Dirindukan by Asma Nadia into the adapted movie by Kuntz Agus. This research is motivated by the addition, reduction and changes in the various content of the story between the novel Surga Yang Tak Dirindukan to its movie adaptation. The method used in this study is a descriptive comparative analysis research method. The theory of actant schema theory and the functional model by A. J. Greimas are some theories that applied in this study. The results of the study prove that there are additions, contractions and changes in the contents of the story between the Surga Yang Tak Dirindukan and the film adaptation. It is hoped that this research can add insight into the repertoire of knowledge, especially regarding the ekranization with a structural approach. Keywords: ecranization, actant scheme, functional model, comparative literature.